Beyond symbolic and substantive: Strategic disclosure of corporate environmental information in China. (28th November 2018) - Meng, Xiaohua; Zeng, Saixing; Xie, Xuemei; Zou, Hailiang
Abstract: Under increasing regulatory pressure to disclose environmental impacts, corporate environmental information disclosure (EID) is becoming more prevalent. However, the motives for EID and disclosure approaches (i.e., symbolic or substantive) remain controversial. Using a sample of data for 742 listed manufacturing firms in China across 3 years, we provide evidence to show that the level of EID is significantly positively associated with a firm's advertising intensity and that firms in moderately competitive industries have a higher propensity for adopting an EID‐based differentiated strategy than firms in stronger or weaker competitive industries. We also find that firms that are more sensitive to environmental issues strategically understate their environmental impact when directly facing consumers. Our results suggest that the implementation of corporate EID is strategic and that firms have strong market motives, even under regulatory pressure to demonstrate legitimacy. We discuss this study's contributions to research on EID theory and implications for strategic EID management.